Pengaruh Motivasi Kerja dan Komitmen Organisasional terhadap Organizational Citizenship Behavior (OCB) dan Kinerja Karyawan (Studi pada Hotel Pelangi di Kota Malang) - Hayati, Evi; Utami, Hamidah Nayati; Susilo, Heru (Universitas Brawijaya, Indonesia, 2011)
The purposes of this research are to prove and to analyze several items, as follows: 1) The influence of working motivation towards the Organizational Citizenship Behavior (OCB) of employees, 2) The influence of organizational commitment towards the Organizational Citizenship Behavior (OCB) of employees, 3) The influence of the Organizational Citizenship Behavior (OCB) towards the employee's working performance, 4) The influence of working motivation towards the employee's performance, 5) The influence of organizational commitment towards the employees' working performance, 6) Indirect influence between the working motivation towards the employees working performance through the Organizational Citizenship Behavior (OCB), 7)Indirect influence of organizational commitment towards the employees working performance through the Organizational Citizenship Behavior (OCB). This research is categorized as explanatory research by applying the research method of path analysis and statistical descriptive, using loading factor from factor analysis. This research is conducted in Pelangi Hotel, Malang by employing the employees' unit analysis. The research indicates that working performance and organizational commitment bring a significant influence towards the Organizational Citizenship Behavior (OCB), the Organizational Citizenship Behavior (OCB) has an influence towards performance, working motivation does not indirectly influence towards performance but indirectly influence the Organizational Citizenship Behavior (OCB), and organizational commitment influences both directly and indirectly through the Organizational Citizenship Behavior (OCB) towards the performance.